Pengaruh Corporate Social Responsibility, Profitabilitas dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Pulungan, Putri Awaliyah Rahma; Suriana, Suriana; Wardani, Widia (Journal of Computer Science and Information System(JCoInS), 2026)
This study aims to determine the effect of Corporate Social Responsibility (CSR), Profitability, and Leverage on Company Value, both partially and simultaneously, in companies that are the research samples. The method used is multiple linear regression analysis with a sample size of 54 companies. The independent variables in this study are CSR, Profitability, and Leverage, while the dependent variable is Company Value. The results of the t-test analysis show that: (1) the CSR variable has a significant negative effect on company value with a calculated t value of -2.293 < t table 1.675 and a significance of 0.026 (< 0.05); (2) the Profitability variable does not have a significant effect with a calculated t value of 0.594 < t table 1.675 and a significance of 0.555 (> 0.05); and (3) the Leverage variable has a negative but not significant effect with a calculated t value of -0.300 < t table 1.675 and a significance of 0.765 (> 0.05). Simultaneously, the F-test results show a calculated F-value of 1.929 < F-table 2.79 with a significance level of 0.137 (> 0.05), indicating that CSR, Profitability, and Leverage collectively have no significant effect on firm value. The Adjusted R² value of 0.019 indicates that the variation in firm value can only be explained by the three independent variables by 1.9%, while the remaining 98.1% is explained by other factors outside this research model. This study implies that companies need to manage CSR and debt use more wisely and improve profitability quality to positively impact firm value.